Engine performance characteristics using microalgae derived dioctyl phthalate biofuel during cold, preheated and hot engine operation. (15th July 2023) - Lodi, Faisal; Zare, Ali; Arora, Priyanka; Stevanovic, Svetlana; Ristovski, Zoran; Brown, Richard J; Bodisco, Timothy
Highlights: Di-octyl Phthalate biofuel blended with diesel in proportions of 10 and 20% was tested. Experiments conducted at cold-to-intermediate-to-hot operating temperatures. During ambient operation, ITE showed dependence on fuel mixing rather than load. MEP and fuel consumption deteriorated with increased O2 content in the blend. Same torque was generated at WOT using all fuels during hot operation. Abstract: This study presents a comprehensive analysis of the engine performance parameters during different temperature-based operating conditions: cold, preheated and hot. Novel blends of Di-octyl Phthalate (DOP) and diesel were prepared by using 10 and 20% DOP ( %v/v ), named B10 and B20, respectively, and compared with ultra-low sulphur diesel (B00). The experiments were conducted on a heavy-duty diesel engine using a custom-designed cold-to-intermediate temperature drive cycle emulating frequent engine stop/start at loads of 100, 50, 75 and 25%, at a constant speed of 1500 rpm. The maximum torque produced by the engine at wide open throttle (WOT), under fully warmed up operation, was within ± 1%, using all fuels. During ambient operation, the improvements in indicated thermal efficiency (ITE) showed dependence on better fuel mixing rather than engine load and improved by 5% and 1% using B20 and B10, respectively, when the engine run progressed from 100% to 25% load. During ambient operation, the indicated mean effective pressure (IMEP) and the brake mean effective pressure (BMEP) were lower by 2 and 4% using B10, and 4 and 7% using B20, when compared to B00, respectively. When the engine was fully warmed-up, the friction mean effective pressure (FMEP) showed an increase of 40 – 80% using the blended fuels, compared to B00 fuel. During ambient operation, the blowby was 10% and 7% lower using B20 and B10 blended fuels, respectively, compared to B00 fuel. During ambient operation, the brake specific fuel consumption (BSFC) was higher by 4 and 10% using B10 and B20 blended biofuels, respectively, compared to B00. Engine parameters such as MEP and SFC were found to deteriorate proportionally with increased oxygen (O2 ) content in the biofuel blends.